2014
DOI: 10.1080/07448481.2014.947990
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Past Bullying Experiences and Psychosocial and Academic Functioning Among College Students

Abstract: Abstract. Objectives: This study examined whether childhood bullying victimization was associated with psychosocial and academic functioning at college. Participants: The sample consisted of 413 first-year students from a large northeastern university. Methods: Students completed an online survey in February 2012 that included items assessing past bullying involvement, current psychosocial and academic functioning, and victimization experiences since arriving at college. Results: Regression analyses indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 38 publications
1
27
1
1
Order By: Relevance
“…with reference to Social Learning Theory, the person might repeat negative behaviour that was rewarded previously (Curwen, McNichol and Sharpe, 2011). It is also influenced by knowledge that those, who are with histories of bullying, have big difficulties to adapt to the environment of higher education institution (Holt et al, 2014), and there exists high enough prevalence of traditional bullying and harassment at schools that sometimes reaches 89.6% (Modecki et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with reference to Social Learning Theory, the person might repeat negative behaviour that was rewarded previously (Curwen, McNichol and Sharpe, 2011). It is also influenced by knowledge that those, who are with histories of bullying, have big difficulties to adapt to the environment of higher education institution (Holt et al, 2014), and there exists high enough prevalence of traditional bullying and harassment at schools that sometimes reaches 89.6% (Modecki et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Transition to higher education institution often raises high requirements for formation of new social connections. Some are trying to establish themselves in the new social hierarchy or to maintain social status they had at school (Rospenda et al, 2013), and others, especially those who suffered school bullying and had difficulty in peer relationships, are likely to demonstrate weaker peer relationships and more difficult development of any relationship (Holt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their literature review, Pörhölä et al (2019) demonstrate the existence of studies to show that being bullied by peers is associated with academic problems and deficiencies in academic achievements in childhood and adolescence, however, they also argue this association may fall away as students grow up. Holt et al (2014), for example, found that past bullying experiences were not associated with academic performance in college. Pörhölä et al suggest that bullying victims at university could be individuals who are very focused on their studies and have high expectations for their study success, and therefore might be particularly sensitive to the feedback and critique they receive of their study performances.…”
Section: Contributions To Construct Validitymentioning
confidence: 99%
“…Although bullying has been widely recognized as a serious issue in elementary and secondary school (e.g., Craig et al 2009;Currie et al 2012;Nansel et al 2001) and in the workplace (e.g., Keashly and Harvey 2005), and its long-term consequences on the psychosocial functioning, academic motivation and study ability of individuals have been found to reach from school year experiences even to higher education (e.g., Espelage et al 2016;Holt et al 2014;Pörhölä et al 2019;Young-Jones et al 2015), relatively little research has examined the prevalence and forms of bullying victimization and perpetration at the university level (Lund and Ross 2016). However, existing studies clearly indicate that bullying does occur among higher education students, and occurrence rates vary substantially between individual studies (Cowie et al 2013;Lund and Ross 2016;Marraccini et al 2015).…”
Section: Introductionmentioning
confidence: 99%